DASHBOARD ANALISIS PERFORMA DAN EKSERGI TURBIN GAS UNIT 3.1 KAPASITAS 235 MW STUDI KASUS PLTGU PT X - FARMA HILAL HAMDI (2023)
Gas Power Plant (PLTG) is one of the most widely used power plants in the industrial world. During its operational period, the components of the PLTG will experience changes in performance and exergy. This study has the objective of monitoring the performance and exergy of the PLTG on an ongoing basis real time with the help of Looker Studio. Thus, when there is a decrease in performance and exergy, there is a flow chart of actions as a basis for actions that need to be taken by PT X. The performance and exergy parameters that can be monitored from the dashboard are: BWR, thermal efficiency, exergy efficiency, exergy, heat in and out, work, heat rate, and SFC. The method used is the ideal Brayton cycle and Looker Studio to monitor performance and exergy real time. Then, make a comparison between the start of the PLTG operating (2011) and currently operating (2023). Based on the research results, the thermal efficiency of the unit has increased by 1.98% from the initial condition. Then, the exergy efficiency of the unit increased by 6.24% from the initial condition. It can be concluded that the higher the applied load, the higher the thermal efficiency and exergy efficiency.